GROWTH PERFORMANCE OF SORGHUM (SORGHUM BICOLOR L.) AS INFLUENCED BY LEGUMES INCORPORATION AND NITROGEN APPLICATION IN SUDAN SAVANNA OF NIGERIA - Adesoji, Aderemi; Ogunwole, J. O.; Ojoko, E. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Soil fertility improvement creates the environment for plant to optimally express itself in growth and development, and subsequently higher yield. The study was set up to determine the influence of incorporated legumes and nitrogen on growth and development of sorghum (Sorghum bicolor L.). Field experiments were carried out in the wet seasons of 2015 and 2016 at the Research Farm of Federal University Dutsin-Ma, Nigeria, The treatments consisted of four levels of N (0, 30, 60 and 90kg N ha -1), and four legumes (Lablab (Lablab purpureus), Mucuna (Mucuna pruriens), Soybean (Glycine max L. Merrill), and Cowpea (Vigna unguiculata L.)) and no legume. SAMSORG 40 variety was used in this experiment. The experiment was laid out in a randomized complete block design and replicated three times. Nitrogen application significantly (P<0.05) increased plant height, number of leaves, total dry weight, leaf-area index and crop growth rate. Fertilization of sorghum with 60kg N ha-1 showed marked increases in growth parameters measured. Application of 60kg N ha-1 was found to be sufficient for remarkable growth and development of sorghum in study area. Incorporation of lablab, mucuna, soybean and cowpea significantly (P<0.05) influenced sorghum growth and development. However, there was no significant difference among plots that received no legume and legume incorporated plots on number of leaves, leaf area index and crop growth rate with exception of plots with incorporated mucuna that gave lowest values for these parameters. Incorporated lablab and cowpea produced better performance on sorghum plant height and total dry matter.